2018
DOI: 10.1108/apjml-05-2017-0093
|View full text |Cite
|
Sign up to set email alerts
|

Do consumers want mobile commerce? A closer look at M-shopping and technology adoption in Malaysia

Abstract: Purpose-Mobile shopping is expected to emerge as a new way of shopping as the Asia Pacific region moves towards the digital era. It is important to understand factors that influence consumers' intentions to adopt this new shopping channel, especially in developing countries such as Malaysia where it has the fastest growing mobile penetration rate in the world. The purpose of this paper is to integrate the Technology Acceptance Model (TAM) and the Theory of Planned Behaviour (TPB), and includes additional varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
111
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(130 citation statements)
references
References 113 publications
13
111
1
5
Order By: Relevance
“…Based on a survey of customer satisfaction Tokopedia in Bali conducted to 45 respondents who on average have shopped 2 to 4 times in the last 3 months, there is 1 person who was not satisfied shopping at Tokopedia and 44 people said they were satisfied shopping at Tokopedia out of the 45 respondents there are 4 respondents said they did not want to shop at Tokopedia again and 41 respondents said they wanted to make repurchase at Tokopedia because the website was easy to use, attractive and innovative features, the items sought were available at Tokopedia, the price of the product was cheap, the price was affordable, offered according to product quality, wide array of products, and finally because many of their friends and favorite celebrities use Tokopedia. In line with the survey, factors that influence online consumer repurchase intentions in Tokopedia illustrate the concept of Brand Leadership which includes perceived value (Wu et al, 2014; Lee et al, 2011), quality and functionality of the website (Sharma and Lijuan , 2015; Lee et al, 2011), innovation power (Ghazali et al, 2018) and popularity (Hsiao et al, 2010). These factors mainly explore consumers' perceptions and attributes of certain e-commerce websites.…”
mentioning
confidence: 90%
“…Based on a survey of customer satisfaction Tokopedia in Bali conducted to 45 respondents who on average have shopped 2 to 4 times in the last 3 months, there is 1 person who was not satisfied shopping at Tokopedia and 44 people said they were satisfied shopping at Tokopedia out of the 45 respondents there are 4 respondents said they did not want to shop at Tokopedia again and 41 respondents said they wanted to make repurchase at Tokopedia because the website was easy to use, attractive and innovative features, the items sought were available at Tokopedia, the price of the product was cheap, the price was affordable, offered according to product quality, wide array of products, and finally because many of their friends and favorite celebrities use Tokopedia. In line with the survey, factors that influence online consumer repurchase intentions in Tokopedia illustrate the concept of Brand Leadership which includes perceived value (Wu et al, 2014; Lee et al, 2011), quality and functionality of the website (Sharma and Lijuan , 2015; Lee et al, 2011), innovation power (Ghazali et al, 2018) and popularity (Hsiao et al, 2010). These factors mainly explore consumers' perceptions and attributes of certain e-commerce websites.…”
mentioning
confidence: 90%
“…A previous study found that TAM was the most used informal context setting on IT adoption; however, it was only limited to the general information on the aspect of technology novelty (Ghazali et al, 2018). Little empirical evidence has found the relationship of TAM's two key constructs with IoT usage.…”
Section: A Perceived Usefulness and Internet Of Things (Iot) Usagementioning
confidence: 99%
“…This study identified the interdependency of both variables. According to Ghazali et al (2018), the ease of using new technology is Previous studies have also shown that social influence does not construct significantly on a voluntary basis, but it works differently when the use of technology is imposed. For this kind of situation, social influence directly affects the intention to use the technology and will fade over time.…”
Section: B Perceived Ease Of Use and Internet Of Things (Iot) Usagementioning
confidence: 99%
“…The rapid migration of technology to mobile has transformed the consumer experience with various aspects of daily life, and created new business opportunities across the market (Chao et al, 2013). For instance, mobile shopping is one of mobile channels have been introduced in the retail market (Ghazali et al, 2018;Phong et al, 2018). Mobile shopping has emerged as a new shopping channel for consumers in line with the rapid technological shift towards mobile transactions (Kalinić et al, 2019).…”
Section: Introductionmentioning
confidence: 99%